Experiment Investigation on Fretting Wear and Wear Debris Performance for the Stem-Cement Interface. (13th August 2015) - Zhang, Lanfeng; Ge, Shirong; Liu, Hongtao
Abstract : After the interface debonding, the body protein fluid is subsequently pumped into stem-cement fretting wear interface, serving as the lubricant. On the stem surface, whether there is the influence of protein absorption on fretting wear or not is considered in this study. The biotribological properties at the stem-cement interface were investigated by SEM. The result of hysteresis loops shows that elasticity and plasticity performance of the frictional interface materials can be damaged by fretting fatigue and material energy dissipation will increase periodically. The wear quantity of cement is mainly influenced by load and displacement. The maximum wear loss of bone cement could reach 1.997 mg. Bone cement and titanium alloy wear debris, whose size distributions are widely spread from 1 to 110 μ m and 5 to 150 μ m, respectively, are shaped like tuber, tear, sheet, strip, and sphere, which will induce the osteocyte damage.